Delay Correction for Pre-Breakdown Phase of Subsonic Stream Discharge in Water. Issue 1 (1st October 2022) - Gao, Chong; Kang, Zhongjian; Zhang, Xianghai
Abstract: Shock waves generated by streamer discharge in water have huge application value to improve unconventional reservoirs. In this paper, experiment platform for high-voltage pulse discharge in water, which beneficial to research the pre-breakdown phase of subsonic streamer discharge in water of high-frequency discharge application scenarios is established. The mechanism of stream discharge and the importance of polarization process were analysed by high voltage theory. The initial time of flow column development was determined based on the time-varying characteristics, and the time of pre-breakdown phase was corrected by using the lightning shock intercept analysis theory. The results show that the polarization process should be incorporated into the pre-breakdown phase. Meanwhile, the initial development time of the flow column is the 3μs of the experimental data. After modification, the polarization process is shortened by 0.9372μs and the delay correction ratio is 24.57% after modification.